An introduction to the science of sport nutrition: why nutrition is important for athletes and games players - Gleeson, Michael (Henry Stewart Talks, 2021)
Sport-specific nutrition guidelines, Energy requirements of sport, Nutrition requirements of sport, Training day nutrition, Match Day nutrition, Recovery nutrition, Supplements to boost performance, Possible benefit vs. risks of dietary supplements, Factors influencing nutrition needs